Measuring monetary policy deviations from the Taylor rule - Madeira, J.; Palma, N. (Economics Letters, 2018)
We estimate deviations of the federal funds rate from the Taylor rule by taking into account the endogeneity of output and inflation to changes in interest rates. We do this by simulating the paths of these variables through a DSGE model using the estimated time series for the exogenous processes except for monetary shocks. We then show that taking the endogeneity of output and inflation into account can make a significant quantitative difference (which can exceed 40 basis points) when calculating the appropriate value of interest rates according to the Taylor rule.